Reasons for attending support groups and organizational preferences: A replication study using the North American Scleroderma Support Group Survey. Issue 3 (October 2019) - Pépin, Mia; Kwakkenbos, Linda; Carrier, Marie-Eve; Peláez, Sandra; El-Baalbaki, Ghassan; Malcarne, Vanessa L; Thombs, Brett D; ,
Peer-facilitated support groups are an important source for receiving disease-related information and support for people with systemic sclerosis (or scleroderma). A recent survey explored reasons for attending systemic sclerosis support groups in Europe and Australia and used exploratory factor analysis to group reasons for attendance into three main themes: (1) interpersonal and social support, (2) disease treatment and symptom management strategies, and (3) other aspects of living with systemic sclerosis. The objective of the present study was to replicate this study in a sample of patients from North America using confirmatory factor analysis. A 30-item survey was used to assess reasons for attendance and organizational preferences among systemic sclerosis patients in Canada and the United States. In total, 171 members completed the survey. In the confirmatory factor analysis, the three-factor model showed good fit to the data (χ 2 (399) = 646.0, p < 0.001, Tucker–Lewis index = 0.97, comparative fit index = 0.97, root mean square error approximation = 0.06). On average, respondents rated 22 (73%) of 30 items as "important" or "very important" reasons for attending support groups. Among organizational preferences, respondents emphasized the importance of the ability to share feelings and concerns, as well as educational aspects. Findings of our study suggest that reasons for attending support groups are similar for patients from Europe, Australia, and North America and that support groups should facilitate social support as well as disease education. These results inform the development of training programs for current and future systemic sclerosis support group leaders across the globe.